Educational game design to improve reasoning skills - Novianti, Nita; Suparman (Asian Journal of Assessment in Teaching and Learning, 2019)
Mathematical reasoning is a modern learning media that is suitable for improving mathematical reasoning. Problem Based Learning is one learning model that can help enhance reasoning. This article aims to design multimedia learning in the form of educational games to enhance students' mathematical reasoning. This research is a type of development research using the Multimedia Development Life Cycle model. The procedure includes six stages, namely concept, design, collecting materials, assembly, testing, and distribution while this research is limited to the design stage. The subjects of the study consisted of teachers and students class 8 of SMP Muhammadiyah 1 Kalasan. The research instruments were observation guides, interview guidelines, and documentation sheets. Observation guidelines are used to retrieve student characteristics data while interview guidelines are used to determine the characteristics of students from the teacher's perspective during the learning process and documentation sheet to get data on curriculum implementation that runs at school. Data were analyzed using qualitative techniques. This research resulted in the design of educational games that were under the needs analysis of students. This educational game is designed to improve students' mathematical reasoning. This research can be extended to collecting, assembly, testing and distribution materials.